A High‐Content Assay for Biosensor Validation and for Examining Stimuli that Affect Biosensor Activity. Issue 1 (1st December 2014) - Slattery, Scott D.; Hahn, Klaus M.
Abstract: Biosensors are valuable tools used to monitor many different protein behaviors in vivo. Demand for new biosensors is high, but their development and characterization can be difficult. During biosensor design, it is necessary to evaluate the effects of different biosensor structures on specificity, brightness, and fluorescence responses. By co‐expressing the biosensor with upstream proteins that either stimulate or inhibit the activity reported by the biosensor, one can determine the difference between the biosensor's maximally activated and inactivated state, and examine response to specific proteins. We describe here a method for biosensor validation in a 96‐well plate format using an automated microscope. This protocol produces dose‐response curves, enables efficient examination of many parameters, and unlike cell suspension assays, allows visual inspection (e.g., for cell health and biosensor or regulator localization). Optimization of single‐chain and dual‐chain Rho GTPase biosensors is addressed, but the assay is applicable to any biosensor that can be expressed or otherwise loaded in adherent cells. The assay can also be used for purposes other than biosensor validation, using a well‐characterized biosensor as a readout for effects of upstream molecules. © 2014 by John Wiley & Sons, Inc.